TRADISI HARI BAIK DALAM PERKAWINAN ADAT BUGIS PINRANG: ANALISIS HUKUM ISLAM DAN EKSISTENSI 'URF DALAM PRAKTIK SOSIAL - Ahmad Zulhaj Bimasakti; Rahmawati; Budiman (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2026)
This study aims to analyze the practice from the perspective of Islamic law and examine its position as ‘urf within the framework of ushul fiqh. This research employs a qualitative method with a normative-empirical approach, utilizing observation, interviews, and literature review. The findings indicate that the tradition does not contradict Islamic law as long as it is not believed to be an absolute determinant of fate, but rather understood as a socio-cultural effort. From the perspective of ‘urf, this practice is categorized as ‘urf shahih since it does not conflict with Islamic texts and contains elements of public benefit. However, it may shift into ‘urf fasid if accompanied by excessive mystical beliefs. Therefore, a proportional understanding is necessary to preserve the tradition without compromising the principle of monotheism in Islam.